THE ROLE OF THE FISHERIES OFFICE IN ENHANCING PATIN CATFISH AQUACULTURE USING POND MEDIA IN LOKSUGA VILLAGE, HAUR GADING SUB-DISTRICT, HULU SUNGAI UTARA REGENCY - hendrayani hendrayani; Maulida Maulida (PPPM STIA Amuntai, 2026)
The potential for developing catfish aquaculture in Loksuga Village, Haur Gading District, Hulu Sungai Utara Regency is considered quite significant and is supported by the designation of the area as a minapolitan zone. However, several problems remain, including suboptimal production, limited facilities and infrastructure, and the uneven role of the Hulu Sungai Utara Regency Fisheries Office in providing guidance to farmers. This study aims to analyze the contribution of the Hulu Sungai Utara Regency Fisheries Office in increasing catfish farming activities in Loksuga Village and to evaluate the effectiveness of the initiatives that have been implemented to support improvements in production and farmers’ welfare. The research uses a qualitative approach with a descriptive qualitative design. Data were collected through interviews, observations, and documentation. Informants were selected using purposive sampling, involving seven respondents. The collected data were analyzed through the stages of data reduction, data display, and conclusion drawing.The results show that the contribution of the Hulu Sungai Utara Regency Fisheries Office in improving catfish aquaculture activities in Loksuga Village is categorized as fairly good. This is reflected in activities such as the preparation of regulations, socialization, mentoring, provision of assistance, and the introduction of innovation and cultivation technology. These programs help farmers improve their aquaculture performance, although their implementation has not yet been fully optimal and tends to be inconsistent. This condition has resulted in less-than-maximum increases in productivity and the sustainability of catfish aquaculture in Loksuga Village, which still requires further improvement.